Macular Edema after Uncomplicated Cataract Surgery: A Role for Phacoemulsification Energy and Vitreoretinal Interface Status?. Issue 3 (May 2015) - Anastasilakis, Konstantinos; Mourgela, Anna; Symeonidis, Chrysanthos; Dimitrakos, Stavros A.; Ekonomidis, Panayiotis; Tsinopoulos, Ioannis
Purpose: To study postoperative macular thickness fluctuations measured by spectral-domain optical coherence tomography (SD-OCT) and to investigate a potential correlation among macular edema (ME) incidence, cumulative dissipated energy (CDE) released during phacoemulsification, and vitreoretinal interface status. Methods: This is a prospective, cross-sectional study of 106 cataract patients with no macular disorder who underwent phacoemulsification. Best-corrected visual acuity measurement, slit-lamp examination, OCT scans were performed preoperatively and 30 and 90 days postoperatively. The intraoperative parameters measured were CDE and total phacoemulsification time. The SD-OCT parameters assessed were central subfield thickness (CST), cube average thickness (CAT), cube macular volume, vitreoretinal interface status, and presence of cystoid or diffuse ME. Results: Four patients (3.8%) developed subclinical ME. Regarding ME, there was no significant difference between patients with presence or absence of posterior vitreous detachment (chi-square, p = 0.57), although 75% of ME cases were observed in patients with attached posterior vitreous. With regard to comparison between eyes with and without subclinical CME incidence, CDE (p = 0.05), phacoemulsification time (p = 0.001), CST at month 1 (p = 0.002), cube macular volume at month 1 (p = 0.039), and CAT at month 1 (p = 0.050) were significantly higher in the subclinical CME group. Conclusions: This study provides evidence that OCT macular thickness parameters increase significantly at first and third month postoperatively and that the incidence of pseudophakic ME can be affected by CDE.